Holliday Cross-Recognition Protein HJURP: Association With the Tumor Microenvironment in Hepatocellular Carcinoma and With Patient Prognosis - Dongcheng Luo; Sina Liao; Yu Liu; Youzhi Lin; Yongqiang Li; XiaoLi Liao (Pathology and Oncology Research, 2022)
Background: Hepatocellular carcinoma is the most common type of primary liver cancer, and it is associated with poor prognosis. It often fails to respond to immunotherapy, highlighting the need to identify genes that are associated with the tumor microenvironment and may be good therapeutic targets. We and others have shown that the Holliday cross-recognition protein HJURP can promote the proliferation, migration, and invasion by hepatocellular carcinoma cells, and that HJURP overexpression is associated with poor survival. Here we explored the potential relationship between HJURP and the tumor microenvironment in hepatocellular carcinoma.Methods: We used the Immuno-Oncology-Biological-Research (IOBR) software package to analyze the potential roles of HJURP in the tumor microenvironment. Using single-cell RNA sequencing data, we identified the cell clusters expressing abundant HJURP, then linked some of these clusters to certain bioprocesses using Gene Set Enrichment Analysis (GSEA). We validated the differential expression of HJURP in tumor-infiltrating CD8+ T cells, sorted by flow cytometry into populations based on the expression level of PD-1. We used weighted gene co-expression network analysis (WGCNA) to identify immunity-related genes whose expression strongly correlated with that of HJURP. The function of these genes was validated based on enrichment in Gene Ontology (GO) terms, and they were used to establish a prognosis prediction model.Results: IOBR analysis suggested that HJURP is significantly related to the immunosuppressive tumor microenvironment and was significantly related to T cells, dendritic cells, and B cells. Based on single-cell RNA sequencing, HJURP was strongly expressed in T cells, erythrocytes, and B cells from normal liver tissues, as well as in CD8+ T cells, dendritic cells, and one cluster of hepatocytes in hepatocellular carcinoma tissues. Malignant hepatocytes strongly expressing HJURP were associated with the downregulation of immune bioprocesses. HJURP expression was significantly higher in CD8+ T cells strongly expressing PD-1 than in those expressing no or intermediate levels of PD1. WGCNA identified two module eigengenes (comprising 397 and 84 genes) related to the tumor microenvironment. We identified 24 hub genes and confirmed that they were related to immune regulation. A prognostic risk score model based on expression of HJURP, PPT1, PML, and CLEC7A showed moderate ability to predict survival.Conclusion:HJURP is associated with tumor-infiltrating immune cells, immune checkpoints, and immune suppression in hepatocellular carcinoma. HJURP-related genes involved in immune responses may be useful for predicting patient prognosis.